A nitroreductase and glutathione responsive nanoplatform for integration of gene delivery and near-infrared fluorescence imaging. Issue 51 (21st May 2020) - Liang, Hong; Bi, Qunjie; Hu, Ao; Chen, Xiaobing; Jin, Rongrong; Song, Xu; Ke, Bowen; Barz, Matthias; Nie, Yu
Abstract : A novel platform rationally integrating indocyanine green analogues and an arginine-rich dendritic peptide with both nitroreductase (NTR) and glutathione (GSH) reduction responsive linkers was developed. Abstract : A novel platform rationally integrating indocyanine green analogues and an arginine-rich dendritic peptide with both nitroreductase (NTR) and glutathione (GSH) reduction responsive linkers was developed. This multifunctional platform can enable selective and efficient gene delivery and specific turn-on fluorescence imaging in tumors.